Impact of two different dual tasks on obstacle crossing in elderly - Emmanuel S da Rocha; Felipe P Carpes (Universidade de São Paulo, 2015)
ABSTRACT The performance of a dual task increases risk of falling during walking in the elderly. Such impact of a dual task may depend on its complexity regarding information processing. Therefore, different dual task configurations may elicit different demands for information processing. We investigated whether different dual task configurations can differently affect the performance of obstacle crossing in the gait of elderly. Ten independent elderly performed vertical obstacle crossing while performing two dual tasks during walking: (a) with auditory input (variation of Stroop task), and (b) without auditory input (report the days of the week in reverse sequence). We hypothesized that a dual task effect would be related with the type of dual task input, and the auditory input would require further information processing and therefore could have larger impact on gait. We found that performance of obstacle crossing was similar regardless of the dual task configuration. Both dual task conditions affect the obstacle crossing in the same extent in the elderly.